Prosumage of solar electricity: Tariff design, capacity investments, and power sector effects - Claudia Günther; Wolf-Peter Schill; Alexander Zerrahn (Energy Policy, 2021)
We analyze how tariff design incentivizes households to invest in residential photovoltaic and battery storage systems, and explore selected electricity sector effects. To this end, we develop an open-source electricity sector model that explicitly features prosumage agents and apply it to German 2030 scenarios. Results show that lower feed-in tariffs substantially reduce investments in residential photovoltaics, yet optimal battery sizing and self-generation are relatively robust. With increasing fixed parts of retail tariffs and, accordingly, lower volumetric retail rates for grid consumption, households have lower incentives for self-consumption. As a consequence, optimal battery capacities and self-generation are smaller, and households contribute more to non-energy power sector costs. A cap on hourly feed-in by households may relieve distribution grid stress without compromising PV expansion or prosumage models for households. When choosing tariff designs, policy makers should not aim to (dis-)incentivize prosumage as such, but balance effects on renewable capacity expansion and system cost contribution.
Keywords: C61; Q41; Q42; 330; Prosumage; Retail tariff; Feed-in tariff; Photovoltaics; Battery storage; Renewable energy